Polarization measurement of dielectronic recombination transitions in highly charged krypton ions - Shah, Chintan; Jörg, Holger Eric; Bernitt, Sven; Dobrodey, Stepan; Steinbrügge, René; Beilmann, Christian; Amaro, Pedro; Hu, Zhimin; Weber, Sebastian; Fritzsche, Stephan; Surzhykov, Andrey; Crespo López-Urrutia, José R.; et al. (Physical review. A, Atomic, molecular, and optical physics, 2015)
We report linear polarization measurements of x rays emitted due to dielectronic recombination into highly charged krypton ions. The ions in the He-like through O-like charge states were populated in an electron-beam ion trap with the electron-beam energy adjusted to recombination resonances in order to produce Kα x rays. The x rays were detected with a newly developed Compton polarimeter using a beryllium scattering target and 12 silicon x-ray detector diodes sampling the azimuthal distribution of the scattered x rays. The extracted degrees of linear polarization of several dielectronic recombination transitions agree with results of relativistic distorted-wave calculations. We also demonstrate a high sensitivity of the polarization to the Breit interaction, which is remarkable for a medium-Z element like krypton. The experimental results can be used for polarization diagnostics of hot astrophysical and laboratory fusion plasmas.